2021
DOI: 10.1002/admt.202100083
|View full text |Cite
|
Sign up to set email alerts
|

Fed‐Batch Droplet Nanobioreactor for Controlled Growth of Cyberlindnera (Pichia) jadinii: A Proof‐Of‐Concept Demonstration

Abstract: Improvement of the microorganism's product yield on feedstock is possible by targeted genetic modification, which requires a solid understanding of the species metabolism and genetics. Alternatively, genetic modifications can be introduced randomly such that the chance that a resulting mutant performs better than the original one is small. Consequently, many mutants need to be created and subsequently screened in order to identify the best performing ones. [1] Given the large number of experiments, it is commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…A recent example of a droplet‐based fed‐batch microbioreactor that does allow the repeated and controlled supply of nutrients to a cell‐containing droplet immobilized in a chamber was demonstrated in the lab of the authors. [ 47 ] The design of the geometry in which the nutrient droplets are produced allows a robust periodic on‐demand supply of droplets in a device free of valves, just through the use of a commercially available pressure pump, [ 48 ] see Figure 6G. The authors demonstrated the cultivation of cells under fed‐batch conditions, with the growth rate of the cells inside the immobilized cell‐containing droplet controlled by the concentration of the nutrient‐containing droplets.…”
Section: Microbioreactors For Nutrient‐controlled Cultivation Of Micr...mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent example of a droplet‐based fed‐batch microbioreactor that does allow the repeated and controlled supply of nutrients to a cell‐containing droplet immobilized in a chamber was demonstrated in the lab of the authors. [ 47 ] The design of the geometry in which the nutrient droplets are produced allows a robust periodic on‐demand supply of droplets in a device free of valves, just through the use of a commercially available pressure pump, [ 48 ] see Figure 6G. The authors demonstrated the cultivation of cells under fed‐batch conditions, with the growth rate of the cells inside the immobilized cell‐containing droplet controlled by the concentration of the nutrient‐containing droplets.…”
Section: Microbioreactors For Nutrient‐controlled Cultivation Of Micr...mentioning
confidence: 99%
“…Adapted from Tomasi et al [46] (G) Fed-batch droplet-based microbioreactor comprising of droplet-on-demand junctions (left) for the controlled supply of nutrient droplets to a cell-containing droplet immobilized in a trap (right). Adapted from Totlani et al [47,48] (H) Channel-free approach in which cell containing droplets are bio-printed in a yield stress fluid. This approach has the potential to repeatedly supply reagents to the cell-containing droplets and study cells under controlled conditions.…”
Section: Microfluidic Chamber-based Platformsmentioning
confidence: 99%
See 1 more Smart Citation